Motion capture and industry: A study on practicality, selection factors and decisions - Mohamad Izani, Z. A.; Anthasha, S. N.; Mohamed Eshaq, Ahmad Rafi (2002)
Proceedings of the International Conference on Imaging Science, Systems and Technology and Applications Conference